Net Change in Energy Use from Ridehail Services in Five California Regions - Thomas P. Wenzel (Future Transportation)
Previously, we estimated the net change in energy use from ridehail services in Austin Texas. This estimate was based, in part, on assumptions regarding the number of rides involving two pooled parties and the distance drivers commuted into their service area to begin their driving day. The recent release of a year’s worth of Uber ridehail rides provided to California agencies, as well as recent surveys of driver commute behavior and the previous mode replaced by ridehail services, have enabled more accurate estimates of the net change in energy use from ridehail services statewide and in five regional markets. We find that the net reduction in energy use from more-efficient vehicles and pooled rides does not offset the additional increase in commute and between-ride deadhead kilometers and replacing more efficient modes with ridehail services. The net result is a 96% increase in statewide energy use (ranging from a 75% to a 123% increase in each region).